DC motor control using peripheral interface controller (PIC) / Nur Zakiah Alias - Alias, Nur Zakiah (2003)
This paper discusses the development of a speed controller system for DC motors. The half-controlled single-phase bridge rectifier using MPlab software is use to designed the controller. PIC is used to control the thyristors, where it switches sequentially during positive cycle of the input voltage. To vary the speed of the DC motor, the firing angle (a) of the thyristors is varied by using external data (using 8- bit DIP switch). This will vary the firing angles (a) such to control the output of half controlled single-phase bridge rectifier. The DC voltage produce at the output can be maximum voltage (for high speed) or low voltage (for minimum speed) for the DC motor. In order to make the controlling of the output of certain system via a rectifier easier, it is possible to control the input signal through it. Since the input signals is fed from the half controlled single phase bridge rectifier, there are several interface circuit must be connected to merge the operational of rectifier. When the complete circuit is operating, the input signal setting can be controlled by varying the firing angles (a). Once it controlled, it produces the output voltage as expected. The observation can be made through the shape of waveform where it is represented by mean voltage. As a result, it shows that by using the PIC, the output of rectifier is now having the controlled output where it is suitable to connect with any load such as DC motor to control its speed.